New and easily accessible nitrogen acyclic gold(I) carbenes: structure and application in the gold-catalyzed phenol synthesis as well as the hydration of alkynes - Hashmi, A. Stephen K.; Hengst, Tobias; Lothschütz, Christian; Rominger, Frank (Advanced synthesis & catalysis, 2010)
A series of gold(I) isonitrile complexes were prepared and converted to the corresponding diaminocarbene gold(I) complexes by reactions with primary and symmetrical secondary amines. Twelve crystal structure analyses of the gold(I) complexes could be obtained, in addition NMR studies allowed an analysis of the different diastereomers present in solution. In the gold-catalyzed phenol synthesis these complexes were very successful as pre-catalysts, reaching an unprecedented 3050 turnovers with a problematic substrate. Good conversions in the hydration of phenylacetylene could also be achieved.